Genetic Linkage Map Construction and QTL Mapping for Juvenile Leaf and Growth Traits in Camellia oleifera - Ling Ye; Yu Li; Yanxuan Liu; Lexin Zhou; Jia’ni Li; Tian Liang; Weiwei Xie; Yiqing Xie; Zhizhen Li; Huanhuan Lv; Na Hou; Gang Wang; et al. (Agronomy)
Advancement of the oil tea industry requires the development of high-yielding and superior-quality varieties of Camellia oleifera, a major oilseed crop. However, traditional breeding methods, hampered by lengthy cycles and low selection accuracy, significantly constrain the breeding process. Identifying single nucleotide polymorphisms (SNPs) associated with target traits, and applying molecular marker-assisted selection (MAS) for these traits, can thereby shorten the breeding cycles and amplify the breeding efficiency. In this study, we utilized the hexaploid C. oleifera as the reference genome to identify high-quality SNPs and constructed a high-density genetic linkage map of C. oleifera that spanned 1566.733 cM, included 3097 SNPs, and was anchored to 15 linkage groups. Using interval mapping, we localized quantitative trait loci (QTLs) for 11 juvenile traits in C. oleifera, identifying 15 QTLs for growth traits and 24 QTLs for leaf traits, including 4 stable QTLs. The logarithm of odds (LOD) scores for individual QTLs ranged from 3.48 to 14.62, explaining 9.86–48.61% of the phenotypic variance. We further identified 2 SNPs associated with growth traits (marker11-951 and marker12-68) and 10 SNPs associated with leaf traits (marker11-276, marker11-410, marker11-560, marker13-16, marker13-39, marker13-110, marker13-731, marker14-701, marker14-910, and marker14-1331). These results provide valuable insights into the genetic mapping of key traits in C. oleifera and will contribute to the development of new varieties with high yield and superior quality in the future.